Extremely brief mindfulness interventions for women undergoing breast biopsies: a randomized controlled trial - Coelho, Bertha Andrade [UNESP]; Paiva, Sara de Pinho Cunha; da Silva Filho, Agnaldo Lopes [UNESP] (Springer Nature, 2018)
Purpose: Mindfulness-based programs can reduce stress and help practitioners to have positive attitudes in their daily lives. This randomized controlled trial evaluated the impact of brief Mindfulness interventions on quantitative and qualitative stress parameters in patients undergoing imaging-guided breast biopsies. Methods: Eighty-two women undergoing percutaneous imaging-guided breast biopsy were randomized into two groups: MBI group or standard care group. One week before the biopsy procedure, on the waiting room and during the biopsy procedure, the MBI group was exposed to mindfulness techniques and the standard care group received supportive dialogue from the biopsy team. Participants completed questionnaires measuring depression, anxiety and stress, demographics, and medical history, besides evaluating their pain experience through a visual analogue scale for pain and had their systolic and diastolic blood pressure, initial and final temperate, heart rate, oxygen saturation, and salivary cortisol measured. Results: Participation in the mindfulness intervention group was associated with reduced levels of perceived stress, blood pressure, heart rate, and oxygen saturation compared to participation in the standard care group (P values < 0.05). No difference was observed regarding salivary cortisol levels, peripheral temperature, and pain perception between the two studied groups. Conclusion: Results indicate that an extremely brief mindfulness intervention is a feasible intervention, suggesting that Mindfulness-based programs may be beneficial to reduce discomfort in acutely stressful settings.
Keywords: Breast biopsy; Mindfulness; Salivary cortisol; Stress markers